Un patrimoine pour la marche. Les sentiers vignerons de Nancy - Xavier Rochel; Anne Hecker; Alexandre Verdier (Cybergeo)
The ancient footpaths around Nancy used to be frequented for the exploitation of vineyards. Nowadays, wine growing has utterly stopped but the footpaths have remained. They are a much-appreciated heritage for local inhabitants. Using a historical GIS, we mapped the network of footpaths as it is now and as it used to be at the beginning of the 19th Century, using the Napoleonian cadastre which was elaborated between 1809 and 1833. The original network amounted to a linear total of 92 km of footpaths, of which only 49 km remain. This dwindling process has nothing to do with the disappearance of vineyards, since they were replaced by family gardens, and the practice of an occasional pleasure walk has maintained the pedestrian traffic. But the urban and peri urban slopes where these footpaths are set are much coveted for urbanization, and they are the only available spaces for bypass routes between the densely-built city and the surrounding, protected natural spaces. The network of footpaths thus appears to be under a constant risk of dislocation.